Kalkulacja kosztów kształcenia w uczelni wyższej na podstawie rachunku kosztów działań - Klaus, Agata; Kowalski, Michał (Calculation of Teaching Costs Using Activity Based Costing, 2007)
Universities require a wide range of cost information to deal with a variety of management decisions. Using such techniques as Activity-Based Costing (ABC) in teaching area, give them a possibility co gain better understanding of teaching costs, assess the financial viability of different courses/programs and determine the cost-effectiveness of different teaching methods. This paper presents a way in which the ABC can be used in calculating teaching costs. It describes the steps involved in implementing the ABC in a selected department of Wroclaw University of Technology and gives some examples of the profits which result from using the ABC.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 257-267